A survey of perceived risk and protective behaviours towards COVID-19 in 2020 in Iraqi Kurdistan - Karwan M-Amen; Sherzad A Shabu; Kazhan I Mahmood; Nazar P Shabila (Journal of Infection in Developing Countries)
Introduction: Human perceptions and behavioural responses to the risk of epidemics have always been crucial factors in studying and containing disease spread. This study aims to assess and understand the risk perception and the behavioural response of a sample of the population in the Kurdistan Region toward COVID-19.